PENERAPAN MEDIA E-COMIC UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V DI SEKOLAH DASAR - Herawati, Silviana; Nurani, Dwi Cahaya; Susiloningsih, Esti (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2025)
Through the use of digital e-comic media combined with the Problem Based Learning (PBL) model, this study aims to improve the critical thinking skills of fifth-grade students at SD Negeri 001 Palembang in the 2025–2026 academic year on the water cycle topic. This research employed Classroom Action Research (CAR) as its methodology and was conducted in two cycles. A total of 25 students from class 5A participated as research subjects. Tests, observations, and documentation were used as data collection methods. Based on the research findings, students’ understanding increased from the first to the second cycle. Only three students (12%) met the Minimum Mastery Criteria (MMC), and the average pretest score was only 47.2. After the implementation of Cycle I, 16 students (64%) achieved the MMC, and the average score increased to 71.6. In Cycle II, all students (100%) exceeded the MMC, with an average score of 82.4. These findings indicate that the improvement of students’ understanding of the water cycle material through the use of the Problem Based Learning approach and e-comic media was successful.